1997
DOI: 10.1016/s0272-6963(97)00014-4
|View full text |Cite
|
Sign up to set email alerts
|

Linking performance drivers in production planning and inventory control to process choice

Abstract: This study investigates how process choice relates to production planning and inventory control decisions. We empirically examine the validity of deductively derived patterns about these types of decisions. More importantly, we look for normative insights by exploring how production planning and inventory control decisions affect operations performance. Our findings show that production line and continuous flow plants use more of a level production strategy, and carry less raw material and work‐in‐process inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 12 publications
1
53
0
Order By: Relevance
“…The decision on process choice should be arranged in line with the aggregate plan, production scheduling and materials management to improve firm's performance, as noted by Safizadeh and Ritzman (1997). Like manufacturing type, these four process types also provide different impacts on the relationship among strategic sourcing, e-procurement and performance in achieving competitive advantages.…”
Section: H1mentioning
confidence: 99%
“…The decision on process choice should be arranged in line with the aggregate plan, production scheduling and materials management to improve firm's performance, as noted by Safizadeh and Ritzman (1997). Like manufacturing type, these four process types also provide different impacts on the relationship among strategic sourcing, e-procurement and performance in achieving competitive advantages.…”
Section: H1mentioning
confidence: 99%
“…When market uncertainty is high (in terms of quantity and timing), a MTO business model ( w h e r e p r o d u c t i o n p l a n n i n g i s m a d e o n a c t u a l o r d e r s r a t h e r t h a n o n f o r e c a s t ) i s recommended (Safizadeh, 1997). An MTO business model allows to eliminate finished goods inventories and reduces the firm's exposure to financial risk -as production is initiated until a customer order is received -but usually spells long customer lead times and large order backlogs (Gupta, 2004).…”
Section: Model Proposalmentioning
confidence: 99%
“…As the risk of stockpiling based on un-accurate sales forecasting is avoided by completely precluding building up anticipation stocks, a chase strategy can be used, where the expected demand is tracked and the corresponding capacity is computed, raising it or lowering it accordingly (Buxey, 2003). Safizadeh (1997) suggested that when following a chase strategy, a job shop should be used. A job shop uses generalpurpose equipment and a multi-skilled work force (grouped around the process), which provides a high degree of flexibility and capability that allows the profitable manufacturing of low-volumes of customized products.…”
Section: Model Proposalmentioning
confidence: 99%
See 2 more Smart Citations